Effects of ginseng on peripheral blood mitochondrial DNA copy number and hormones in men with metabolic syndrome: A randomized clinical and pilot study. (February 2016) - Jung, Dong-Hyuk; Lee, Yong-Jae; Kim, Chun-Bae; Kim, Jang-Young; Shin, Seung-Hun; Park, Jong-Ku
Highlights: We examine the effect of red ginseng on mitochondrial function, hormones and metabolic syndrome in men with metabolic syndrome. We show that red ginseng increase growth hormone and mitochondria DNA copy number after 4 weeks treatment. We did not show an improvement of metabolic syndrome component except diastolic BP, after 4 weeks treatment. Abstract: Background: It has been observed that mitochondrial dysfunction is associated with an increased risk of metabolic syndrome. There is growing evidence that hyperactivity of the hypothalamus-pituitary-adrenal (HPA) axis and hormone (testosterone and growth hormone) deficiency may lead to metabolic syndrome. Recent studies have reported that ginseng treatment improves mitochondrial and HPA-axis function and increases anabolic hormone secretion. Objectives: The objective of this study was to investigate the effect of red ginseng (RG) on metabolic syndrome, hormones, and mitochondrial function using leukocyte mitochondrial DNA copy number in men with metabolic syndrome. Methods: We performed a randomized, double-blind, placebo-controlled study in 62 subjects who were not taking drugs that could affect their metabolic function. A total of 62 men with metabolic syndrome were randomly assigned to either an RG group (3.0 g/day) or a placebo group for 4 weeks. We analyzed changes in metabolic syndrome components, leukocyte mitochondrial DNA copy number, hormones (total testosterone, IGF-1, cortisol, and DHEAS) and inflammatory markers (C-reactive protein, ferritin) from baseline to 4 weeks. Results: Significant improvement in mitochondrial function (95% CI −44.9 to −1.3) and an increase in total testosterone (95% CI −70.1 to −1.0) and IGF-1( P  = 0.01) levels were observed in the RG group when compared with the placebo group. Diastolic blood pressure (95% CI 2.0–9.4) and serum cortisol (95% CI 1.1–5.5) significantly decreased in the RG group. Conclusions: We found evidence that RG had a favorable effect on mitochondrial function and hormones in men with metabolic syndrome.